2001
DOI: 10.1021/es000278r
|View full text |Cite
|
Sign up to set email alerts
|

Selective Trapping of Organochlorine Compounds in Mountain Lakes of Temperate Areas

Abstract: The study of fish concentrations and sediment inventories in 19 European high mountain lakes (40-67 degrees N) shows that a fraction of organochlorine compounds (OCs), the less volatile compounds (LVC; subcooled liquid vapor pressure < or = 10(-2.5) Pa), are trapped in the higher locations. This general trend is not significantly influenced by possible local sources. Compound distribution is related to average air temperatures. The phase-change pseudoenthalpies calculated from the sediment inventories closely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
178
3
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 240 publications
(200 citation statements)
references
References 34 publications
14
178
3
3
Order By: Relevance
“…High levels of metals (such as mercury, Hg, and lead, Pb) and persistent organic pollutants such as polychlorinated biphenyls (PCBs) are present in the tissue of freshwater fish in arctic and alpine lakes (Grimalt et al, 2001;Vives et al, 2004a). This attests to the mobility and transport of these substances in the atmosphere (Carrera et al, 2002) and their concentration in cold regions (Fernandez & Grimalt, 2003).…”
Section: Toxic Substancesmentioning
confidence: 99%
See 1 more Smart Citation
“…High levels of metals (such as mercury, Hg, and lead, Pb) and persistent organic pollutants such as polychlorinated biphenyls (PCBs) are present in the tissue of freshwater fish in arctic and alpine lakes (Grimalt et al, 2001;Vives et al, 2004a). This attests to the mobility and transport of these substances in the atmosphere (Carrera et al, 2002) and their concentration in cold regions (Fernandez & Grimalt, 2003).…”
Section: Toxic Substancesmentioning
confidence: 99%
“…In Europe, mountains and remote ecosystems are directly influenced by temperature changes and are subject to the accumulation of persistent organic pollutants (POPs) (Grimalt et al, 2001). Rivers and lakes in these environments provide information on the transfer mechanisms and impact of these compounds in headwater regions.…”
Section: Toxic Substancesmentioning
confidence: 99%
“…Numerous studies have reported concentration gradients of organic contaminants in mountain environments that increase with increasing elevation, a process termed ''mountain coldtrapping'' [4,36,37]. It has been proposed that this process is controlled largely by the temperature dependence of organic vapor partitioning into rain, snow, and aerosols [38].…”
Section: Elevation Gradients In Pesticide Concentrationsmentioning
confidence: 99%
“…Many studies have been conducted worldwide to assess POP levels and distribution in mountain areas (e.g. Grimalt et al 2001;Barra et al 2005;Wang et al 2006Wang et al , 2007Nizzetto et al 2008;Moeckel et al 2008;Tremolada et al 2009a).…”
Section: Introductionmentioning
confidence: 99%